Bond finance, bank credit, and aggregate fluctuations in an open economy - Roberto Chang; Andrés Fernández; Adam Gulan (Bank of Finland, 2016)
Corporate sectors in emerging markets have noticeably increased their reliance on foreign financing, presumably reflecting low global interest rates. The evidence also shows a rebalancing from bank loans towards bonds. To study these developments, we develop a dynamic open economy model where these modes of finance are determined endogenously. The model replicates the stylized facts following a drop in world interest rates; in particular, rebalancing towards bonds occurs because bank credit becomes relatively more expensive, reflecting the scarcity of bank equity. More generally, the model is suitable for studying interactions between modes of finance and the macroeconomy.
URN:NBN:fi:bof-201608121372
Keywords: E32; E44; F41; G31; 330